Evaluación del ADN espermático de llamas utilizando azul de toluidina. - Carretero, M.I. (2009)
Toluidine blue stain (TB) binds to DNA, allowing differentiation of spermatozoa according to the degree of chromatin condensation. The objectives of this study were to adapt a technique for evaluating sperm chromatin in llamas, determine chromatin condensation patterns in llamas using TB and determine if it is possible to use dithiothreitol (DTT) as a positive control for the stain. Two fixation times with ethanol 96° (2 and 30 minutes) and 3 incubation times with 1% DTT (30 s, 1.5 min and 3 min) were studied. Staining patterns observed were: light blue (negative, without alteration in the normal chromatin condensation), light violet (intermediate, some degree of decondensation), dark violet (positive, high degree of decondensation). No significant differences were observed between fixation times, either in samples with or without DTT. To conclude, it was possible to simplify the TB stain and determine the different patterns in llama spermatozoa. It was proved that incubation with DTT can be used as a positive control for the stain and to evaluate individual susceptibility to decondensation in vitro.